Motivasi Siswa Memilih Sekolah, Prestasi Belajar dan Perencanaan Arah Karier Siswa Sekolah Menengah Atas - Roshinta Erezka (Indonesian Journal of Counseling and Development, 2022)
Education is part of a long way trip to a career. Education is also a significant element of one's efforts in preparing to enter the world of occupations. The suitability of employment with the state itself is believed will bring them a better life in the future. More specifically, for high school students, a decision on the selected type of education has direct implications for the career, office, or aspiring to a career after completing his studies at the level of education he passes. The results of this study indicate that the three hypotheses tested significantly correlated. There is a significant correlation between students' motivation and learning achievement in career planning. These findings suggest that students' motivation for school and learning achievement can not be ignored in addition to other variables that are suspected of having links with the planning of career direction. The supervising teacher has expected to develop through a credible form of counseling program activities more effectively and creatively as well as provide career information to students in planning a career direction